Overexpressing the Sedum alfredii Cu/Zn Superoxide Dismutase Increased Resistance to Oxidative Stress in Transgenic Arabidopsis - Li, Zhen; Han, Xiaojiao; Song, Xixi; Zhang, Yunxing; Jiang, Jing; Han, Qiang; Liu, Mingying; Qiao, Guirong; Zhuo, Renying (Frontiers in Plant Science, 2017)
Superoxide dismutase (SOD) is a very important reactive oxygen species (ROS)-scavenging enzyme. In this study, the functions of a Cu/Zn SOD gene (SaCu/Zn SOD), from Sedum alfredii, a cadmium (Cd)/zinc/lead co-hyperaccumulator of the Crassulaceae, was characterized. The expression of SaCu/Zn SOD was induced by Cd stress. Compared with wild-type (WT) plants, overexpression of SaCu/Zn SOD gene in transgenic Arabidopsis plants enhanced the antioxidative defence capacity, including SOD and peroxidase (POD) activities. Additionally, it reduced the damage associated with the overproduction of hydrogen peroxide (H2O2) and superoxide radicals (O2•-). The influence of Cd stress on ion flux across the root surface showed that overexpressing SaCu/Zn SOD in transgenic Arabidopsis plants has greater Cd uptake capacity existed in roots. A co-expression network based on microarray data showed possible oxidative regulation in Arabidopsis after Cd-induced oxidative stress, suggesting that SaCu/Zn SOD may participate in this network and enhance ROS-scavenging capability under Cd stress. Taken together, these results suggest that overexpressing SaCu/Zn SOD increased oxidative stress resistance in transgenic Arabidopsis and provide useful information for understanding the role of SaCu/Zn SOD in response to abiotic stress.